The transformation of Spirals into S0 galaxies in the cluster environment - D'Onofrio, Mauro; Marziani, Paola; Buson, Lucio (Frontiers in Astronomy and Space Sciences, 2015)
We discuss the observational evidences of the morphological transformation of Spirals into S0 galaxies in the cluster environment exploiting two big databases of galaxy clusters: WINGS (0.04<z<0.07)andEDisCS(0.4<z<0.8). The most important results are: 1) the average number of S0 galaxies in clusters is almost a factor of ∼ 3 − 4 larger today than at redshift z ∼ 1; 2) the fraction of S0’s to Spirals increases on average by a factor ∼ 2 every Gyr; 3) the average rate of transformation for Spirals (not considering the infall of new galaxies from the cosmic web) is: ∼ 5 Sp→S0’s per Gyr and ∼ 2 Sp→E’s per Gyr; 4) there are evidences that the interstellar gas of Spirals is stripped by an hot intergalactic medium; 5) there are also indirect hints that major/minor merging events have played a role in the transformation of Spiral galaxies. In particular, we show that: 1) the ratio between the number of S0’s and Spirals (NS0/NSp) in the WINGS clusters is correlated with their X-ray luminosity LX ; 2) that the brightest and massive S0’s are always close to the cluster center; 3) that the mean Se ́rsic index of S0’s is always larger than that of Spirals (and lower than E’s) for galaxy stellar masses above 10^9.5M⊙; 4) that the number of E’s in clusters cannot be constant; 5) that the largest difference between the mean mass of S0’s and E’s with respect to Spirals is observed in clusters with low velocity dispersion. Finally, by comparing the properties of the various morphological types for galaxies in clusters and in the field, we find that the most significant effect of the environment is the stripping of the outer galaxy regions, resulting in a systematic difference in effective radius and Se ́rsic index.